Legal Protection of Consumer Personal Data In Online Loan Transactions - Redi Rahadian Bagaskara (Pelopor Publikasi Akademika, 2024)
The financial sector, especially through online loan applications, has seen new opportunities thanks to technological advances, especially in the field of communications. Although online loans are easy to use, they also present risks regarding personal data security and unsafe lending practices. Along with the popularity of online loans, crimes in the digital world, such as data theft and misuse of information, are increasing. Although vulnerable to detrimental lending practices, especially illegal loans that have not been registered with the Financial Services Authority (OJK), people with low incomes see online loans as an attractive option. The aim of this research is to study how the protection of consumer personal data in online loan transactions is protected by law, especially considering the phenomenon of violations and unprofitable lending practices. This research examines how Law no. 27 of 2022 concerning Personal Data Protection (UU PDP) protects personal data and how it impacts borrowers socially and psychologically. This research shows regulatory and practical innovation in dealing with the problem of personal data leakage which is detrimental to consumers when borrowing money via the internet. Through regulatory analysis and case studies, this research is expected to provide insight into how effective personal data protection is in online loan transactions. Therefore, this research helps build better regulations and efforts that protect customers in the ever-growing era of online lending.